2017
DOI: 10.1111/1750-3841.13681
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability in Oil‐in‐Water Emulsions with Quercetin or Rutin Under Iron Catalysis or Riboflavin Photosensitization

Abstract: The effects of quercetin and rutin on the oxidative stability of oil-in-water (O/W) emulsions were tested under riboflavin (RF) photosensitization in the presence or absence of FeCl . The degree of oxidation in O/W emulsions was determined by headspace oxygen content, conjugated dienes, and lipid hydroperoxides. Quercetin chelated more metal than did rutin in iron catalyzed O/W emulsions. Generally, 0.1 mM quercetin and rutin was oxidative while 0.5 and 1.0 mM quercetin and rutin was antioxidative in O/W emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…All four antioxidants studied, possessed multiple hydroxyl (OH) groups along with carbonyl moieties, which meant they each possessed multiple sites for metal chelation (Leopoldini et al, 2006). Rutin hydrate exhibited the lowest ferrous iron chelation activity, which was found to be significantly lower than the closely structurally related quercetin; a finding which was echoed in another recent study (Yi et al, 2017). Rutin hydrate possesses one less chelating site than quercetin due to the replacement of an OH group with a rutinose dissacharide group (C. Hider et al, 2001).…”
Section: Antioxidant Activitiesmentioning
confidence: 81%
See 2 more Smart Citations
“…All four antioxidants studied, possessed multiple hydroxyl (OH) groups along with carbonyl moieties, which meant they each possessed multiple sites for metal chelation (Leopoldini et al, 2006). Rutin hydrate exhibited the lowest ferrous iron chelation activity, which was found to be significantly lower than the closely structurally related quercetin; a finding which was echoed in another recent study (Yi et al, 2017). Rutin hydrate possesses one less chelating site than quercetin due to the replacement of an OH group with a rutinose dissacharide group (C. Hider et al, 2001).…”
Section: Antioxidant Activitiesmentioning
confidence: 81%
“…Therefore, increased hydrophobicity is perhaps also why quercetin combatted LO more effectively than rutin hydrate, in addition to superior antioxidant potency displayed in Figure 2. Furthermore, the smaller molecular size of quercetin compared to rutin hydrate would allow it to locate more efficiently at the O/W interface leading to greater antioxidant concentrations (Yi et al, 2017).…”
Section: Antioxidant Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PV of the mayonnaise added with BHT was lower than that of the control, those added with the buckwheat hull extracts were even lower, suggesting that the buckwheat hull extracts might retard oxidation in early stages. Yi et al (2017) reported that rutin and quercetin have ability to increase oxidative stability of lipids in an O/W emulsion, suggesting that well known major flavonoids in buckwheat hulls such as rutin and quercetin may contribute to retardation of lipid oxidation in mayonnaise. TBA values of all the mayonnaise samples continuously increased during storage (Fig.…”
Section: Oxidative Stability Of Lipids In Mayonnaisementioning
confidence: 99%
“…It has been reported that due to the presence of 3′−4′dihydroxy (catechol structure) in the B ring and 3-OH and 5-OH groups in the C ring, quercetin can provide a balance between entering to the lipid droplet surface for inhibiting lipid oxidation and interacting with Fe 3+ in the aqueous phase (Choulitoudi et al, 2021;Huber et al, 2009;Yang et al, 2015). Yi et al (2017) studied that quercetin mainly located at the oil-water interface of corn oil-in-water emulsions under riboflavin photosensitization and found that its high concentrations (0.5 and 1.0 mmol/kg) showed a metal chelating ability with an antioxidant activity of 75.5% and 80.4% against the formation of lipid hydroperoxides, respectively.…”
Section: Quercetinmentioning
confidence: 99%